Characterizing the enhanced neuronal apoptosis in ATRX knockout mice - Goodall, Emma (University of Ottawa (Canada), 2009)
Mutations in ATRX, a SWI/SNF-like chromatin remodeling protein, cause the very rare ATR-X mental retardation syndrome (OMIM# 30032). The ATR-X syndrome is characterized by global developmental delay and 95% of cases are diagnosed with severe to profound mental retardation. Previous experiments have established a developmental requirement for ATRX and have suggested a role for ATRX in corticogenesis. Conditional forebrain specific ATRX -/- mice were shown to have a loss of cortical mass, which resulted from a 12-fold increase in apoptosis during early stages of corticogenesis. We show that the loss of ATRX results in a loss of neurons but does not affect the differentiation of astrocytes. Furthermore, we demonstrate enhanced p53mediated apoptosis in the ATRX knockout model. Consistent with this, we demonstrated elevated activity levels of caspase-9 and -3, key apoptotic factors. Additionally, we show an upregulation of the pro-apoptotic genes Bid and Peg3 in ATRX knockout samples. Together these results suggest that ATRX may play a critical role in promoting neuronal survival by inhibiting p53 mediated apoptosis.
Keywords: Biology, Cell.